Building an Inclusive, Green and Low-Carbon Economy CCICED Annual Policy Report 2022. (Springer Nature Singapore : Imprint: Springer, 2023)
This open access book introduces the major environmental green development issues from six major themes carbon neutrality, nature-based solution, watershed management and climate adaptation, BRI green development, sustainable food supply chain, ecosystem-based integrated ocean management focusing on the progress of China's environment and development policies from 2021 accomplishments. It is based on the research outputs of CCICED in the year of 2021, which marks China's start point of implementation of its 14th Five-Year Plan when world economy also strived to recover from the pandemic. .